Kajian Geografi Politik Terhadap Perolehan Suara Partai Politik Berdasarkan Struktur Ruang Kota Kendari - Madiha Almultazimah; Irfan Ido; Jamal Harimudin; Jufri Karim (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
Kendari as the provincial capital, is the political center. Political parties are essential in recruiting legislative candidates to positions of influence. So that, people require information regarding political maps. This study aims to: (1) Analyze the distribution and dynamics of changes in the voting based on the area of the city service center system and the administrative area of Kendari City; (2) Analyze the supporting factors of the winning political party's voting base. This study was conducted based on data elections in 2014 and 2019, data used is secondary data of party vote data, which were examined using spatial analysis, which included percentage analysis and Location Quotient analysis first, followed by qualitative analysis. The findings of this study are (1) PAN received the highest votes in 2014 but was replaced by PKS in 2019. In two periods, the four spatial structures underwent different based changes. The central city, the education center, port and industrial center and the terminal center in 2014 became the base of Demokrat, PDIP, PBB, and PAN while in 2019 was replaced by PKB, PAN, Demokrat, and PKS; (2) Vision, mission, and money politics are the most influential factors supporting a party's victory.